The Effect of Compound Physical and Skill Exercises on the Development of Explosive Strength and Some Offensive Skills for Basketball Players U18 - Hussein , Ammar; Hanoon, Wasan (Journal of Physical Education, 2022)
The research aimed at designing compound physical and skill exercises as well as identifying their effect on the development of explosive strength and some offensive skills in basketball players U18. The researchers used the experimental program with one group but two tests; pretests and posttests. The subjects are (12) players from the national center for gifted in basketball. The program was applied for (8) weeks to conclude that compound exercises are effective in developing legs and arms explosive strength as well as developing skill leading to development in offensive skill. The researchers recommended using scientific bases for designing training programs while stressing rest periods due to their effect developing physical traits including explosive power.